28 A cochrane review of strategies to increase adoption of the ottawa ankle rules and reduce unnecessary imaging. (20th August 2018) - Zadro, Joshua; Dario, Amabile; Maher, Christopher
Abstract : Objectives: The aim of this review is to establish the effectiveness of existing strategies to increase adoption of the Ottawa Ankle Rules (OARs) and reduce ankle/foot imaging. Method: We will conduct a Cochrane systematic review according to the Methodological Expectations of Cochrane Intervention Reviews standards, within the Cochrane Musculoskeletal Group. A comprehensive keyword search (combining terms synonymous with 'implementation' and 'Ottawa Ankle Rules') will be performed in MEDLINE, EMBASE, CINAHL, Cochrane CENTRAL, Scopus and Web of Science from the earliest record to the time of search. Additional articles will be identified by hand-searching references lists and forward searching of included articles. We will include randomised controlled trials, uncontrolled trials, and interrupted time-series investigating strategies to increase adoption of the OARs. The primary outcome will be documented adherence to the OARs. The proportion of unnecessary ankle/foot imaging requests and the total number of ankle/foot imaging requests will be secondary outcomes. Two reviewers will independently perform the selection of studies, extract key data (e.g. trial characteristics, intervention parameters, outcomes), and assess the risk of bias of included studies. Results: We anticipate to have extracted all study data by the conference and are confident we will be able to present preliminary results. Conclusions: Nearly 10% of people suffer an ankle injury in their life; but although less than 20% have a fracture, 70%–95% receive imaging. In the absence of a fracture, imaging does not inform management and exposes patients to unnecessary/potentially harmful radiation. The OARs are a clinical decision tool with nearly 100% sensitivity for ruling out ankle/foot fractures, thereby indicating those who don't require imaging. These rules have been validated in numerous countries, endorsed in practice guidelines for over two decades, and more recently included in Choosing Wisely lists. Successful implementation of the OARs could reduce unnecessary ankle/foot imaging and time spent in emergency departments. However, the OARs aren't commonly used in practice. Identifying effective strategies to increase adoption of the OARs could reduce unnecessary ankle/foot imaging among various healthcare professionals and guide implementation activities to reduce low-value care across health disciplines.